Sincronização na Nuvem de Dados Sensoriais de Pecuária - Thiago de Oliveira Soares (2024)
Cattle farming plays a crucial role in the Brazilian economy, being essential to the country's Gross Domestic Product (GDP). Therefore, the efficiency and sustainability of this sector are fundamental to maintaining its competitiveness. In this context, technological innovations represent indispensable tools for enhancing livestock monitoring and management. The e-Cattle platform emerges as an integrated solution for precision livestock farming, offering advanced features for effective herd monitoring and data-driven decision support. This work focuses on the development of two critical components for the e-Cattle platform: the first aimed at synchronization of locally collected sensory data with the cloud, ensuring the uniformity and integrity of the information essential for accurate analyses and informed decisions. The second component aims at implementing a dedicated memory manager, designed to prevent excessive data accumulation, ensuring operational continuity and efficiency of the platform. Both innovations are fundamental for optimizing cattle management, representing significant steps toward smarter and more sustainable production.